MEDICAL ETHICS, LOCAL WISDOM AND PROFESSIONALISM - Sajid DarmadiPura (Faculty of Medicine, Universitas Andalas, 2014)
AbstractRecengy the problem of profession, professional, professionalism, and ethics in medicinehave been attracting much the public, the media, the professionals, and even also the medicalpractitioners.This may be stimulated by several cases involving medical professionals exposedby the press, originaiing from the decreasing comprehension on the above named terms' Theline differentiating profession from business is too becoming vague. Professionalism that shouldcontain also high ethical moral standards and humanitarian values beside the knowledge andskill is decreasing in comprehension among the medical practitioner and other professionals ingeneral. A clear normative definition of each of those terms is needed. As lndonesian physicians,we should refer and apply the basic principles stated in Pancasila, i.e' the philosophical moralbasis of the lndonesia foundation in providing medical and health service. Further our reflectionsgo on to whether the principles of Pancasila can replace the ethical principles of Bioethics, thewestern concept. Accepting the western completely would likely mean accepting the culturalimperialism, while replacing the western values or principles totally is unnecessary consideringthat many of the western conform our local wisdom'Keywords: Profession, professionalism, medical ethics, Pancasila, local wisdom'transculturalism and value recipi